Automated volumetry of the mesiotemporal structures in antibody-associated limbic encephalitis. Issue 7 (2nd September 2014) - Wagner, Jan; Witt, Juri-Alexander; Helmstaedter, Christoph; Malter, Michael P; Weber, Bernd; Elger, Christian E
Abstract : Objective: Limbic encephalitis (LE) is an autoimmune mediated disease leading to temporal lobe epilepsy, mnestic and psychiatric symptoms. In recent years, several LE subforms defined by serum antibody findings have been described. MRI usually shows volume changes of the amygdala and hippocampus. However, studies quantifying longitudinal volume changes in the acute disease stage are lacking. Methods: The aim of this retrospective observational study was to evaluate and quantify these volume changes by applying a fully automated volumetric approach to serial MRIs of 28 patients with antibody-associated LE. The results were compared with those of 28 age-matched and gender-matched healthy controls and analysed separately for the different antibody profiles and correlated with clinical parameters. Antibody profile analyses were exploratory due to the relatively small sample sizes. Results: We found distinct volumetric and clinical courses depending on the associated antibody. While LE associated with voltage-gated potassium channel-complex antibodies (VGKC-LE) showed highly significant larger volumes of both the amygdala and the hippocampus within the first 12 months after disease onset, LE associated with glutamic acid decarboxylase antibodies (GAD-LE) only displayed greater amygdala volumes at this disease stage. Both subgroups showed a reduction of the amygdala and hippocampus volumes during follow-up with higher volume changes in VGKC-LE. Conclusions: These differences in the volumetric evolution corresponded to distinct clinical courses in terms of a more severe initial symptomatology regarding seizure, mnestic and psychiatric disturbances in VGKC-LE, which improved rapidly, corresponding to the evolution of the volumetric changes. In contrast to this, patients with GAD-LE were less severely affected at disease onset, showing a more unmodulated and chronic disease course during follow-up.